Comparison of ovarian stimulation in follicular and luteal phases in an ovarian cycle (DuoStim) in patients with poor ovarian response - Elham Naghshineh; Rezvan Aalami-harandi; Nasrin Heydari; Vahid Shahabi; Nasrin Borumandnia; Safa Salehi (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background Infertility is a global problem that refers to the absence of pregnancy after 12 months of intercourse without using contraception. Assisted reproductive techniques (ART) are a treatment technique for infertile patients. Poor ovarian response to stimulation (POR) is one of the challenges in the field of ART. POR refers to people in whom, despite appropriate ovarian stimulation, the number of oocytes retrieved is less than expected. Several ovarian stimulation protocols are applied in POR patients, but the best protocol is not defined. One of the protocols used in POR patients is the "double stimulation in the same ovarian cycle" (DuoStim) protocol. During the DuoStim protocol, both follicular and luteal phases of an ovarian cycle are stimulated. It allows us to retrieve oocytes twice in one ovarian cycle. In the current study, ovarian stimulation in follicular and luteal phases in an ovarian cycle in patients with the poor ovarian response is compared. Results Twenty-six infertile patients with poor ovarian enrolled. They had a mean ± standard deviation age of 36.3 ± 3.15 years. The duration of follicular phase stimulation (FPS) was shorter than luteal phase stimulation (LPS) (p value = 0.003). The total dose of gonadotropin was significantly lower in FPS than in LPS (p value = 0.013). Significantly fewer total oocytes were retrieved after FPS than after LPS (p value = 0.001). Conclusion This study supports the putative benefits of LPS in infertile women with POR. Utilizing the DuoStim strategy in people with poor ovarian response caused more oocytes to be retrieved. Trial registration: irct.ir identifier: IRCT20221001056068N1, 11/22/2022, https://www.irct.ir/trial/66187.